The stonekeeper - Kibuishi, Kazu 1978- (New York Graphix, 2008)
"After the tragic death of their father, Emily and Navin move with their mother to the home of her deceased great-grandfather, but the strange house proves to be dangerous. Before long, a sinister creature lures the kids' mom through a door in the basement. Em and Navin, desperate not to lose her, follow her into an underground world inhabited by demons, robots, and talking animals. Eventually, they enlist the help of a small mechanical rabbit named Miskit. Together with Miskit, they face the most terrifying monster of all, and Em finally has the chance to save someone she loves"--Publisher's web site
"An imprint of Scholastic."
2
Keywords: Graphic novels